If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15m + -4(2m + -6) = 38 Reorder the terms: 15m + -4(-6 + 2m) = 38 15m + (-6 * -4 + 2m * -4) = 38 15m + (24 + -8m) = 38 Reorder the terms: 24 + 15m + -8m = 38 Combine like terms: 15m + -8m = 7m 24 + 7m = 38 Solving 24 + 7m = 38 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 7m = 38 + -24 Combine like terms: 24 + -24 = 0 0 + 7m = 38 + -24 7m = 38 + -24 Combine like terms: 38 + -24 = 14 7m = 14 Divide each side by '7'. m = 2 Simplifying m = 2
| 3*3*3-(31-2*3)= | | -2(3-7x)=22 | | 15-7(x-2)=1 | | (2sin2x)/x | | u^2-32u+31=0 | | 10x+9(3)=8 | | 1/4d_ | | f(x)=ln(81sin^2x) | | 3+4x=13+9x | | 2a^3b^0/c^2)-3 | | An=n^2+3n | | Tan^2x-5tanx-6=0 | | 2y=-3x+8 | | -4(7x+1)=-312 | | -5=-20+-25 | | 12x^2-132x+252=0 | | 30=7+N-4+8 | | 40=-2(23-y)+3(y-3) | | -8=17+6z | | 6(x+6)=-9+3x | | 7=3(23-x)+2(x-2) | | 7=t^2-6t | | -3p-48=0 | | 3r+11=2-3(3r+3) | | -7+x=-3x+25 | | 3ln(5x+4)=22 | | 4(4x-9)-6=4(x-4)+46 | | 16x^2-7t=17t-9 | | 36-6x=14+5x | | 2u^2+13u+15=0 | | (4x^2)+4x+(4y^2)-32y-335=0 | | 4x^2-147=0 |